Agroterrorism in Indian Context - Datta, Sibnarayan; ., Vanlalhmuaka; Dwivedi, Sanjai Kumar (Defence Life Science Journal, 2020)
In the context of change in global scenario of terrorism and economic competition, the risk of deliberate attack on agriculture is increasing. In a country, like India, whose economy is largely dependent on agriculture produce and exports, any such malicious attack can grossly destabilise the socio-economic structure. Additionally, an attack on major food crops can lead to potential threat to food security, subsequently, leading to destabilised law and order situation of a state. It is therefore very important to understand the risks and threats of agroterrorism for a given country in order to be prepared for any such circumstance. In this review we discuss different aspects of agroterrorism, its history, possibilities of such incidences in Indian scenario and mitigation strategies, which can be achieved through regular surveillance of pathogens in vulnerable crop ecosystems. We also describe a recent episode of outbreak of cotton leaf curl disease in the Northwest Indian cotton growing region and discuss it from the perspective of a possible threat on one of the most important economic crops of our country.